1979
DOI: 10.3102/00346543049004517
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis—Prescriptive Teaching: A Critical Appraisal

Abstract: The dominant instructional model within special education, Differential Diagnosis-Prescriptive Teaching, involves the assessment of psycholinguistic and perceptual motor abilities that are presumed necessary for learning basic academic skills. Based on the differential pattern of ability strengths and weaknesses resulting from this assessment, individual remedial prescriptions are prescribed.In this article five assumptions underlying this model are identified. Also presented is a comprehensive review of resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 59 publications
(33 reference statements)
1
40
0
Order By: Relevance
“…Hartlage and Lucas (1976), in that the Koppitz and Beery tasks present generally higher correlations with the WISC-R than the WRAT, and in that correlations of the Koppitz and Beery tasks with the WRAT are not higher than those of Full Scale IQ with the WRAT. The correlations of both visual-motor tasks with the WRAT in the present sample are similar in magnitude to those reported by Hartlage and Lucas and generally exceed the .35 minimum recommended by Arter and Jenkins (1979). Table 3 presents the partial correlations of Beery and Koppitz scores with the WRAT, adjusting for the effect of WISC-R Full Scale IQ.…”
Section: Resultssupporting
confidence: 67%
“…Hartlage and Lucas (1976), in that the Koppitz and Beery tasks present generally higher correlations with the WISC-R than the WRAT, and in that correlations of the Koppitz and Beery tasks with the WRAT are not higher than those of Full Scale IQ with the WRAT. The correlations of both visual-motor tasks with the WRAT in the present sample are similar in magnitude to those reported by Hartlage and Lucas and generally exceed the .35 minimum recommended by Arter and Jenkins (1979). Table 3 presents the partial correlations of Beery and Koppitz scores with the WRAT, adjusting for the effect of WISC-R Full Scale IQ.…”
Section: Resultssupporting
confidence: 67%
“…One critique oflearning styles identified five different reviews on matching learning styles, spanning 14 years and examining over 90 studies (Stahl, 1999), and it failed to find empirical evidence that matching learning styles improves learning. One of those reviews (Arter & Jenkins, 1979) examined 14 studies and concluded that the use of remedial prescriptions based on differential patterns of ability strengths and weaknesses (so called Differential Diagnosis-Prescriptive Teaching) is an approach that cannot be justified, stating that "Children do not appear to profit from current applications of Differential Diagnosis-Prescriptive Teaching" (p. 517). They further stated, u •• .it is not surprising that DD-PT has not improved academic achievement, since most ability assessment devices have inadequate reliability and suspect validity" (p. 549).…”
Section: Downloaded By [University Of Western Ontario] At 05:43 13 Apmentioning
confidence: 97%
“…One of the first articles that led to skepticism of the existence of student learning styles was that published by Arter and Jenkins (1979), which pertained to those teaching in special education but had implications for all educators. The authors referred to the "term 'differential diagnosis' which Downloaded by [Texas A & M International University] at 22:20 14 August 2015 refers to the process of assessing the learning characteristics of a child so that instruction can be matched to individual learning needs" (p. 517).…”
Section: Reliability and Validity Of Learning Stylesmentioning
confidence: 98%